ANALISIS KINERJA PERUSAHAAN TAHUN 2021-2022 DENGAN METODE EVA PADA PT. ACE HARDWARE INDONESIA.TBK - August Halomoan Siregar; Mario Andrias Kiton (Halu Oleo University, 2024)
Realizing good company financial performance is the dream of all companies stakeholders, especially company financial managers, company owners and investors. Financial performance as reported through Financial Reports can be analyzed using various methods including using the Economic Value Added (EVA) method. Recently, many companies have implemented the EVA method as a method for assessing company performance. Economic Value Added (EVA) is a very effective assessment system for assessing a company's financial performance over a certain period. This research aims to analyze the financial performance of the company PT. ACE Hardwared, Tbk uses the Economic Value Added (EVA) method. This research is quantitative descriptive research using secondary data in the form of Financial Reports for the 2021-2022 period obtained from the Indonesia Stock Exchange (BEI). The research results for 2021, 2022 show a positive EVA (>0) so that the company is deemed to have been able to create economic added value after the company paid all of the company's obligations to its investors.